Transformational Leadership and Employee Commitment: The Roles of Conflict Management and Organisational Culture at SNEL_Congo - Chinyabuuma Bengibabuya Esther; Meika Kurnia Puji Rahayu (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study investigates the impact of transformational leadership on employee commitment at the Société Nationale d'Électricité (SNEL) in the Democratic Republic of Congo. It further examines the mediating function of conflict management and the moderating influence of organizational culture in this relationship. A quantitative methodology was employed to gather primary data from 150 employees, which was subsequently analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings demonstrate that transformational leadership markedly improves employee commitment and favorably affects conflict management. Conflict management was identified as a partial mediator in the association between transformational leadership and employee commitment, indicating that efficient conflict resolution strategies are essential for converting leadership behaviors into favorable employee results. Moreover, organizational culture substantially influences this link, with supportive and collaborative cultures enhancing the effect of transformative leadership. This research enhances the existing literature in three significant aspects. Initially, it amalgamates leadership, conflict resolution, and organizational culture into a cohesive analytical framework. Secondly, it offers empirical findings from a previously under-explored African public sector context. Third, it underscores the significance of contextual and relational dynamics in influencing employee commitment. The results provide actionable insights for enhancing leadership efficacy and organizational success in comparable institutional contexts.